Do the Ends Strengthen the Means? An Examination of the Link Between Purpose in Life and Academic Misconduct Among College Students. Issue 4 (1st October 2016) - Yu, Hongwei; Glanzer, Perry; Johnson, Byron
Abstract: Scholarship addressing academic misconduct has started to examine the relationship between academic misconduct and student virtues such as self-control. To date, however, no one has studied the relationship between academic misconduct and life purpose. To address this gap, the authors drew upon a large sample of 2, 503 college students and used the structural equation modeling technique to examine this relationship. Although no direct relationship was found, the authors did find an indirect, negative association between students' purpose in life and self-reported engagement of academic misconduct.